CHARACTERIZATION OF ENERGY BAND GAP THIN FILM BaTiO3 – BaZr0.5Ti0.5O3 USING DIFUSION REFLECTANCE SPECTROSCOPY (DRS) METHOD - Dewi, Rahmi; Manalu, Wesly Arianto; Asrinaldo, Brian Noval; Rini, Ari Sulistyo; Yanuar, Yanuar (Spektra: Jurnal Fisika dan Aplikasinya, 2023)
Ferroelectric material is a dielectric material that has a high dielectric constant value so that it can be made in the form of thin films. Its application is based on electro-optical properties, one of which is the infrared thermal switch. This paper aims to determine the bandgap energy (Eg) of a 0.3BaTiO3 – 0.7BaZr0.5Ti0.5O3 thin film. The 0.3BaTiO3 – 0.7BaZr0.5Ti0.5O3 thin film is a semiconductor material with the valence band and conduction band separated by an energy bandgap (Eg). Thin films of 0.3BaTiO3 – 0.7BaZr0.5Ti0.5O3 were grown on FTO substrates using the sol-gel method. The films of 0.3BaTiO3 – 0.7BaZr0.5Ti0.5O3 were annealed at different temperatures of 700°C, 750°C and 800°C within 1 hour. Characterization was carried out using Ultra Violet Visible (UV-Vis) spectroscopy to determine Eg using the Diffusion Reflectance Spectroscopy (DRS) method. The DRS method was found to be better for solid materials considering the scattering component. The UV-Vis characterization results show that an increase in annealing temperature causes a decrease in Eg. For example the values ​​at 700°C, 750°C and 800°C are 3.5 ± 0.01 eV; 3.3±0.01 eV and 3.2±0.01 eV. The decrease in Eg is related to the diffusion of Barium Titanate (BaTiO3) ions into the Barium Zirconium Titanate (BZT) lattice forming a new sub-gap which in turn gives BT-BZT the ability to absorb lower light. Lower light absorption means more capable optics for multilayer systems.